Sustainable synthesis of antibacterial 3-aryl-2H-benzo[b,1,4]oxazin-2-ones via SNAr Csp2–Csp2 coupling - Salehzadeh, Fatemeh; Esmkhani, Maryam; Noori, Milad; Javanshir, Shahrzad; Iraji, Aida; Mahdavi, Mohammad (Frontiers in Chemistry, 2024)
In the pursuit of sustainable synthetic methods, we applied nucleophilic aromatic substitution (SNAr) under microwave-assisted conditions to synthesize 3-aryl-2H-benzo [b][1,4]oxazin-2-one derivatives, including the natural product cephalandole A. This metal-free carbon-carbon coupling method demonstrates a more sustainable approach by eliminating the need for metal catalysts and offering efficient reaction conditions, resulting in good yields (55-82%) with reduced reaction times (7-12 min) and simplified workup processes.Regarding the critical need for new antibacterial agents against antibiotic-resistant pathogens, we conducted an in silico molecular docking study to evaluate the antibacterial potential of the synthesized derivatives. This computational approach allowed us to predict the binding affinity and interaction profiles of the compounds with key bacterial targets, identifying 3-(1H-indol-3-yl)-6-methyl-2H-benzo [b][1,4]oxazin-2one (6b) as a particularly promising candidate for further biological evaluation. By integrating sustainable synthesis with in silico antibacterial screening, this research contributes not only to the development of ecofriendly synthetic pathways in pharmaceutical chemistry but also to the urgent global effort to discover novel antibacterial agents.